Metreleptin for the treatment of progressive encephalopathy with/without lipodystrophy (PELD) in a child with progressive myoclonic epilepsy: a case report - Stefania Pedicelli; Luca de Palma; Caterina Pelosini; Marco Cappa (BMC, 2020)
Abstract Background A number of genetic syndromes associated with variants in the BSCL2/seipin gene have been identified. Variants that cause skipping of exon 7 are associated with progressive encephalopathy with/without lipodystrophy (PELD), which is characterized by the development of progressive myoclonic epilepsy at a young age, severe progressive neurological impairment, and early death, often in childhood. Because the genetic basis of PELD is similar to that of congenital lipodystrophy type 2, we hypothesized that a patient with PELD may respond to treatments approved for other congenital lipodystrophic syndromes. Case presentation We describe a 5-year-old boy with an extremely rare phenotype involving severe progressive myoclonic epilepsy who received metreleptin (a recombinant analogue of leptin) to control metabolic abnormalities. At the age of two, he had no subcutaneous adipose tissue, with hypertriglyceridemia, hypertransaminasemia and hepatic steatosis. He also had a moderate psychomotor delay and generalized tonic seizures. At 4 years, he had insulin resistance, hypercholesterolemia, hypertriglyceridemia, mild hepatosplenomegaly and mild hepatic steatosis; he began a hypolipidemic diet. Severe psychomotor delay and myoclonic/myoclonic atonic seizures with absences was evident. At 5 years of age, metreleptin 0.06 mg/kg/day was initiated; after 2 months, the patient's lipid profile improved and insulin resistance resolved. After 1 year of treatment, hepatic steatosis improved and abdominal ultrasound showed only mild hepatomegaly. Seizure frequency decreased but was not eliminated during metreleptin therapy. Conclusions Metreleptin may be used to control metabolic disturbances and may lead to better seizure control in children with PELD.